PENGARUH PERSEPSI KEMUDAHAN, KUALITAS LAYANAN, DAN RISIKO KEAMANAN TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET DALAM TRANSAKSI KEUANGAN - Susanti, Ni Luh Putu Rima; Dwiana Putra, I Made Pande (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The rapid development of technology affects many community activities, one of which is activity in transactions. This study aims to obtain empirical evidence regarding the influence of perceived convenience, service quality, and security risk on decisions to use e-wallets in financial transactions. The population of this study are users of e-wallet applications in financial transactions in Denpasar City, especially students of the Accounting Study Program class of 2019, Faculty of Economics and Business, Udayana University. The sampling method used in this study is non-probability sampling, namely purposive sampling. Based on the results of the analysis, it was found that perceived convenience and service quality have a positive effect on the decision to use e-wallets. Security risks have a negative effect on e-wallet usage decisions. This research provides theoretical implications regarding the support of the Technology Acceptance Model, as well as practical implications for e-wallet users and providers regarding perceived convenience, quality of service, and security risks in decisions to use e-wallet.